2013
DOI: 10.1111/roie.12074
|View full text |Cite
|
Sign up to set email alerts
|

Export Spillovers of FDI on China's Domestic Firms

Abstract: This paper examines the horizontal and vertical export spillovers of foreign direct investment (FDI) on China's manufacturing domestic firms by using firm-level census data over the period of 2000-03. Based on a Heckman two-step procedure combining first differencing and instrumental variable regression techniques, it is found that FDI has had a positive impact on the export value of domestic firms mainly through backward technology spillovers and a positive impact on the export-to-sales ratio of domestic firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 28 publications
(40 reference statements)
3
57
0
1
Order By: Relevance
“…They also find that FDI-related spillovers from the rest of the world are heterogeneous but not curvilinear and the size of productivity spillovers depends on firm size and product quality. Chen et al (2013) [12] examined the horizontal and vertical export spillovers of foreign direct investment (FDI) on China's manufacturing domestic firms by using firm-level census data over the period 2000-2003 They found that FDI has had a positive impact on the export value of domestic firms mainly through backward technology spillovers and a positive impact on the export-to-sales ratio of domestic firms through horizontal export-related information spillovers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also find that FDI-related spillovers from the rest of the world are heterogeneous but not curvilinear and the size of productivity spillovers depends on firm size and product quality. Chen et al (2013) [12] examined the horizontal and vertical export spillovers of foreign direct investment (FDI) on China's manufacturing domestic firms by using firm-level census data over the period 2000-2003 They found that FDI has had a positive impact on the export value of domestic firms mainly through backward technology spillovers and a positive impact on the export-to-sales ratio of domestic firms through horizontal export-related information spillovers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spillovers from IFDI are regarded as an important source of knowledge in developing countries (e.g. Javorcik 2004; Kneller and Pisu 2007;Sheng et al 2011;Chen et al 2013). …”
Section: Reverse Knowledge Spillovers From Ofdi: Theory and Literaturementioning
confidence: 99%
“…On the other hand, it can crowd local firms out of the product market, and also offers completion in local labour and resources markets (e.g. Aitken and Harrison 1999;Hu et al 2005;Chen 2011Chen , 2015bFu 2011;Sheng et al 2011;Chen et al 2013). The net effects of horizontal knowledge spillovers from IFDI on domestic firms are inconclusive (Gorg and Greenaway 2004).…”
Section: Reverse Knowledge Spillovers From Ofdi: Theory and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Vertical FDI knowledge spillovers arise through forward and backward industrial linkages between FDI firms and domestic firms within the supply chain (for example, Chen et al 2013;Girma et al 2004;Javorcik 2004;Kneller and Pisu 2007). When FDI firms provide higher-value intermediate materials for their customers or when they transfer product knowledge to their suppliers, they contribute to domestic firms' productivity and competitiveness in upstream and downstream industries, in turn increasing local economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%